Associations between respiratory signs, thoracic CT findings and results of tracheobronchoscopy and bronchoalveolar lavage in dogs. (29th January 2022) - Osathanon, Rungrote; Lamb, Christopher R.; Church, David B.
Abstract: Background: Several diagnostic techniques are used in dogs with signs of respiratory disease. The aims of the present study are to estimate the relative sensitivities and associations between the results of diagnostic tests in dogs with respiratory conditions. Method: A retrospective cross‐sectional study of dogs referred for investigation of respiratory signs. Associations between clinical signs, thoracic CT findings, tracheobronchoscopic findings, cytology results and bacterial culture results were tested using binary logistic regression. Results: One hundred and thirty‐three dogs were included. Abnormalities were detected by cytology, tracheobronchoscopy, CT and bacterial culture in 91%, 88%, 80% and 25% cases, respectively. There were associations between cough and bronchial lesions on thoracic CT (odds ratio [OR] 2.6, 95% confidence interval [CI] 1.1–6.4, p  = 0.037), and between cough and neutrophilic inflammation on cytology (OR 4.5, 95% CI 1.3–15.8, p  = 0.020). Bronchial foreign body at bronchoscopy was associated with pulmonary consolidation on CT (OR 8.0, 95% CI 1.6–41.7, p  = 0.013) and with positive bacterial culture (OR 10.9, 95% CI 2.1–57.0, p  = 0.005). In dogs with normal thoracic CT, abnormalities were detected by cytology, tracheobronchoscopy and bacterial culture in 89%, 77% and 23% cases, respectively. Conclusion: Airway cytology and tracheobronchoscopy provided useful information for diagnosis in many dogs with respiratory signs that had a normal thoracic CT.